Research on Disability Grading Based on ICF Functional Framework: Empirical Evidence From Zhejiang Province, China - Liu, Huan (Frontiers in Public Health, 2021)
Through assignment method, the total score of disability in multiple dimensions is obtained, and it is divided into five functional states of severe disability, partial disability, moderate disability, mild disability and health according to the score, and the probability of death is constructed. Using the CLHLS database 2011 and 2014 tracking survey data, by constructing a multi-state transition probability matrix, the empirical calculation of the multi-state disability transfer probability; with the help of the sixth national census data, we estimated maintenance time of each state, life expectancy, etc. The results show that the three-year transfer probability of the initial healthy elderly is the highest, and the mortality rate is also the lowest.It can be found that the disability state transition probability measurement based on the data is more accurate than the model estimation; the disability scale and life expectancy estimated based on the multi-state transition probability matrix are more reliable.